Continuous low-dose chemotherapy plus inhibition of cyclooxygenase-2 as an antiangiogenic therapy of glioblastoma multiforme - Tüttenberg, Jochen; Grobholz, Rainer; Korn, Tobias; Wenz, Frederik; Erber, Ralf; Vajkoczy, Peter (Journal of cancer research and clinical oncology, 2005)
Purpose: Glioblastoma multiforme (GBM) represents the prototype of an angiogenic tumor. Recently, the continuous low-dose scheduling of chemotherapeutic drugs in combination with an inhibition of cyclooxygenase-2 (COX-2) has been suggested as a novel anti-angiogenic approach. The aim of this study was to evaluate the safety and activity of continuous low-dose temozolomide (TMZ) plus the COX-2 inhibitor rofecoxib in patients with newly diagnosed GBM. Methods: In vitro, endothelial cells were characterized by a tenfold higher sensitivity to TMZ than glioma cells. Consequently, a subgroup of patients with incompletely resected GBM (n=13) was divided into three groups aiming at a dose escalation to 1/10 of the daily MTD for TMZ: (A) TMZ 10 mg/m(2) every third day and rofecoxib 25 mg/d; (B) TMZ 10 mg/m(2)/d and rofecoxib 25 mg/d; (C) TMZ 5 mg/m(2) twice a day and rofecoxib 12.5 mg twice a day. COX-2, VEGF, VEGF Receptor-2, and CD34 were assessed immunohistochemically, in the clinical setting. Results: The mean follow-up period was 15 months. We observed no severe toxicity attributable to the therapy. Quality of life was not impaired. For the whole study population, median time to progression and overall survival were 8 months and 16 months, respectively. Immunohistochemistry suggested that tumors with higher vessel densities were characterized by a significantly better control than those with lower vessel densities. Conclusions: Continuous low-dose TMZ plus rofecoxib is feasible, safe, and maintains good quality of life. This study is indicative of an anti-angiogenic efficacy of continuous low-dose TMZ plus rofecoxib in GBMs, especially in those tumors that are characterized by a high angiogenic activity.